Contribution of the Social Sciences and Human Health Sciences: Example of a multidisciplinary research - Gómez Cardona, Liliana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2012)
Cultural pluralism and social diversity go through different social contexts in the contemporary world, exerting different impacts on official institutions. In the context of health care of a cosmopolitan city as Montreal, new projects of investigation and intervention are necessary, in order to assess how different population groups come into contact with such services.At the research level, it is essential to create interdisciplinary collaborations in order to examine the clinical situations in the light of the various constituent elements: social, cultural and ethnic ones.In this article, I present some reflections derived from interdisciplinary research among anthropologists and clinicians, whose central theme turned around functional gastrointestinal disorders in the pediatric population.This work in medical anthropology allows to document and analyze the speeches of families and children around the perception of that health problem, as well as practices and solutions implemented in order to relieve pain and achieve a welfare state.The main focusesI share in this article are theoretical and methodological references used in the anthropology discipline, which will be illustrated with the help of some extracts of interviews.Beyond simply listing the results of the research, I show an example of collaboration between anthropology and pediatrics, which opens perspectives for future research and applications in regard to relationships between families, communities and institutional healthservices.